Legal Discovery Method for Non-Muslim Heirs as Recipients of Wasiat Wajibah - Fawzi, Ramdan; Rojak, Encep Abdul; Mujahid, Ilham; Sahid, Mualimin Mochammad (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
The Islamic inheritance system has not fully accommodated the problem of inheritance distribution in the reality of society, especially the rights of non-Muslim heirs. Therefore, in several of its decisions, the Supreme Court of the Republic of Indonesia grants rights to non-Muslim heirs through wasiat wajibah. This study discusses wasiat wajibah in Islamic Law and Positive Law and the method of finding law used by Supreme Court judges in rulings on non-Muslim heirs. The research method uses normative juridical with a legislative, conceptual and case approach. The results of the study show that Islamic law (Quran, Hadith and Fiqh) has expressly regulated the provisions for the settlement of inheritance between heirs, the procedure for the division and transfer of the heir's property to the heirs, as well as the reasons for obtaining a share of the inheritance as well as the reasons that hinder the heirs. The method of legal discovery used by the Supreme Court Judges in the decision of non-Muslim heirs uses an extensive interpretation with a deepening of the Compilation of Islamic Law concerning wasiat wajibah for adopted children and adoptive parents. Wasiat Wajibah are a way out to get a share for non-Muslim heirs, because the recipients are not hindered due to religious differences. This decision is an extension of the Compilation of Islamic Law on wasiat wajibah . The Supreme Court's decision can be used as a reference for the Religious Court in deciding the same case.